The efficiency of the collection of tax revenues in the municipality of Guamo Tolima, during the periods of 2015 to 2017 (2018)
The good public administration developed by a territorial entity allows obtaining a set of benefits where they are worthy for effectively managing their resources, putting other adhesions into practice such as implementation of processes, improvement of quality, service and attention to citizens is contributing to the development indirectly, because it is not enough to implement their policies if they speak for themselves of the growth of the municipality, where a gain at the social level is the maximum welfare of the community